Prisoner radicalization and terrorism detention policy institutionalized fear or evidence-based policy-making? - Veldhuis, Tinka (Routledge frontiers of criminal justice, 2016)
Correctional policies for Islamist violent extremist offenders are often based on the premise that prisons can be hotbeds of radicalization. The perception that inmates are susceptible to violent extremist belief systems has given rise to a fervent international public, political, and scholarly debate and has led to the introduction of drastic, often expensive policies to counter the threat of prison radicalization. This book is the first to present a detailed and systematic case study of the decision-making and implementation process behind terrorism detention policy. It will be essential reading for students, scholars and policymakers researching criminal justice, terrorism and extremism.